Osteogenic effects of electrophoretically deposited Sr-doped calcium silicate coatings on titanium - Wang, Zi; Du, Yimin; Zhang, Shunlin; Li, Hongliang; Yang, Jinghong; Yan, Jiyuan; Li, Zhong; Liu, Jinhui; Liu, Juncai (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTitanium (Ti) implants are mechanically reliable but lack osteoinductivity. Calcium silicate (CaSiO3) coatings improve bioactivity but degrade rapidly. Strontium (Sr), a bone-regulating ion, enhances osteoblast function and suppresses bone resorption. Incorporating Sr into CaSiO3 may synergistically improve coating stability and osteogenic performance.ObjectiveTo develop Sr-doped CaSiO3 coatings with varying Sr concentrations and evaluate their effects on osteogenesis, identifying the optimal formulation for Ti surface functionalization.MethodsSr-CaSiO3 powders (0.05, 0.10, 0.20 mol Sr) were synthesized by sol-gel and applied to Ti via electrophoretic deposition. The morphology and composition of the coating were analyzed using XRD, SEM, and EDS, and its effects on osteoblast-like cells (MC3T3-E1) proliferation, differentiation, mineralization, and Wnt/β-catenin pathway activation were evaluated.ResultsThe 0.10 mol Sr group exhibited optimal surface structure and Ca/P ratio (1.73). It significantly enhanced ALP expression, calcium nodule formation, and β-catenin nuclear translocation (p < 0.001), indicating superior osteogenic induction.ConclusionSr-doped CaSiO3 coatings enhance osteogenesis in a dose-dependent manner. The 0.10 mol Sr concentration provides the best combination of structural stability, osteoinductive capacity, and long-term bioactivity. These findings highlight the potential of Sr-doped CaSiO3 coatings as a promising surface modification strategy to improve the integration and clinical success of Ti implants in bone repair and regenerative medicine.